Self-Compassion in the Relationship between Personality Traits and Bedtime Procrastination - Seyedeh Zahra Mohtarami Zavardeh; Mitra Ashoori; Saeideh Bazzazian (Journal of Social Behavior and Community Health, 2024)
Background: Since sleep is considered an important factor for the physical and mental health of humans, it is very important to pay attention to its quantity quality and abnormalities during it. Therefore, the purpose of this research is to investigate the role of self-compassion mediation in the relationship between Personality traits and bedtime procrastination. Methods: The research method was descriptive-correlational. The statistical population included all undergraduate students of the humanities faculties of Tehran University in the academic year of 2022-2023, who were selected through Cluster sampling of 343 students. Data collection tools included the Bedtime Procrastination Questionnaire (BPS), Self-Compassion Questionnaire (SCS), and Neo Personality Questionnaire (FFI-NEO). Finally, the data were analyzed using the Pearson correlation method and structural equations using SPSS version 22 and AMOS version 24 Software. Results: The goodness of fit index for the research model was significant, which indicated the appropriate fit of the model. The result showed that the direct effect of personality and bedtime procrastination was -0.36 and the indirect effect of personality through self-compassion and bedtime procrastination was -0.19. Conclusion: The results of the present study showed that personality and self-compassion play an important role in bedtime procrastination. Therefore, the relations obtained can be used to improve the lifestyle and promote sleep health in students and other people.